The fine feats of the 'Five Cockerels' gang a Yugoslav Marxist-Surrealist epic poem for children - Vučo, Aleksandar 1897-1985; Matić, Dušan 1898-1980 (Brill, 2022)
The Fine Feats of the Five Cockerels Gang is a Marxist-Surrealist Yugoslav epic poem for children, written by Aleksandar Vučo and accompanied by Dušan Matić’s photocollage illustrations and captions. The poem tracks the adventures of five scrappy, resourceful working-class boys who endeavor to free an equally plucky girl from the evil clutches of a convent school (and its fearsome nuns). While weighing in on various contemporary political issues, the story is unpredictable, action-packed and relayed in richly colloquial language. Matić’s photocollages show "what happened in the meantime" between the "songs" (episodes) of the poem, providing clever twists to the linear plot as well as an illustration of the surrealist concepts of time, space and the transformative capabilities of art.
Keywords: Vučo, Aleksandar -- 1897-1985 -- Podvizi družine "Pet petlića"; Vučo, Aleksandar -- 1897-1985; Matić, Dušan -- 1898-1980; Geschichte 1933; Illustration; Kinderbuch; Surrealismus; Jugoslawien; Quelle